The Relationship Between Psychological Quality Education and Mental Health Level of College Students by Educational Psychology - Xu, Ruihong (Frontiers in Psychology, 2022)
To enable all college students to have positive psychological quality and sound personalities, their potential should be fully realized, and their comprehensive ability should be improved to adapt to society. Empirical research is carried out by means of questionnaires, and the relationship between psychological quality education and the mental health level of college students is studied through correlation analysis and regression analysis. Firstly, the problems existing in college students’ psychological quality education are summarized from the perspective of educational psychology through questionnaires. Secondly, the data of college students’ psychological quality education and mental health level are collected, and the general situation and the relationship between college students’ psychological quality education and mental health level are analyzed and discussed by processing the existing data. The research results show that 51% of college students think that psychological quality education is only needed when there is a psychological problem; 47% of college students believe that the current educational content of the school’s psychological quality education focuses on the prevention and solution of students’ psychological problems; 83% of the students consider that the psychological quality education currently carried out by the college still adopts the more traditional teaching methods such as classroom lectures, psychological counseling and special lectures. In the process of predicting college students’ mental health level, psychological resilience plays a significant role, which can predict 21.1% of variables. Psychological resilience and optimism can jointly predict 26.4% of variables. These contents broaden the research field of college students’ psychological quality education, enrich the related research on it, and provide a reference for the intervention of college students’ psychological health in school situations.